Re-establishing agriculture as a priority for development policy in Sub- Saharan Africa - Abdulai, Awudu; Delgado, Christopher L. (International Food Policy Research Institute, 1995)
Three-quarters of the labor force in Sub-Saharan Africa has agriculture as its primary occupation. The concentration of low income countries in this region is high and under the present trends food insecurity will be growing rapidly over the next two decades. Inadequate national agricultural policies in the north and south have contributed to the poor performance of agriculture in Africa. African national investments in agricultural research, extension, and rural infrastructure have often been inappropriate. They have lacked popular participation and private-sector involvement, and have also been affected by recent austerity measures and by reductions in donor assistance to agriculture.